2014
DOI: 10.1371/journal.pmed.1001613
|View full text |Cite
|
Sign up to set email alerts
|

Early Experiences Implementing Pre-exposure Prophylaxis (PrEP) for HIV Prevention in San Francisco

Abstract: Albert Liu and colleagues report early experiences with uptake and delivery of pre-exposure prophylaxis(PrEP)for HIV prevention in three different settings in San Francisco. PrEP can be an important component of a comprehensive HIV prevention program and can complement efforts to increase HIV testing, linkage to care, and early initiation of antiretroviral therapy. Please see later in the article for the Editors' Summary

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
201
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 228 publications
(213 citation statements)
references
References 47 publications
10
201
1
Order By: Relevance
“…2 Despite demonstrated efficacy of antiretroviral pre-exposure prophylaxis (PrEP) in reducing HIV acquisition, evaluation of PrEP uptake and use outside of research settings remains limited. [3][4][5] Commonly cited barriers to PrEP implementation include limited awareness about PrEP, concerns about side-effects, adherence, cost, access, low perceived risk of HIV acquisition, and stigma. 2,4,6,7 Whether and how these barriers affect PrEP uptake and PrEP clinical programs in real-world settings is unknown.…”
Section: 4mentioning
confidence: 99%
“…2 Despite demonstrated efficacy of antiretroviral pre-exposure prophylaxis (PrEP) in reducing HIV acquisition, evaluation of PrEP uptake and use outside of research settings remains limited. [3][4][5] Commonly cited barriers to PrEP implementation include limited awareness about PrEP, concerns about side-effects, adherence, cost, access, low perceived risk of HIV acquisition, and stigma. 2,4,6,7 Whether and how these barriers affect PrEP uptake and PrEP clinical programs in real-world settings is unknown.…”
Section: 4mentioning
confidence: 99%
“…Although MSM are a key population for biomedical HIV prevention, 1,[8][9][10] difficulties communicating about behavior in healthcare settings may hinder implementation. Prior studies have found that mistrust, disclosure difficulties, and internalized homophobia may limit healthcare access and delay presentation for care among MSM.…”
mentioning
confidence: 99%
“…19 Liu and colleagues found that in addition to fear of being stigmatized by family and peers, potential PrEP users sensed judgment and resistance from medical providers providing PrEP. 25 Most notably, among all of these studies, concern around users being labeled as sexually deviant or too sexually adventurous seems to be a critical barrier to widespread acceptance of PrEP use. The insights gained from these exploratory studies highlighting stigma as a barrier are crucial to understand in more depth as biomedical interventions for HIV prevention become more widespread.…”
mentioning
confidence: 99%